Federico Donelli. 2021. Turkey in Africa: Turkey’s Strategic Involvement in Sub-Saharan Africa. Londres: I. B. Tauris. 224 pp. Ebook (PDF) ISBN 9780755636990 - Herrera Esquivel, Andrés (Estudios de Asia y África, 2022)
Federico Donelli. 2021. Turkey in Africa: Turkey’s Strategic Involvement in Sub-Saharan Africa. Londres: I. B. Tauris. 224 pp. Ebook (PDF) ISBN 9780755636990